2015
DOI: 10.1007/s11367-015-0931-6
|View full text |Cite
|
Sign up to set email alerts
|

Meat alternatives: life cycle assessment of most known meat substitutes

Abstract: Purpose Food production is among the highest human environmental impacting activities. Agriculture itself accounts for 70-85 % of the water footprint and 30 % of world greenhouse gas emissions (2.5 times more than global transport). Food production's projected increase in 70 % by 2050 highlights the importance of environmental impacts connected with meat production. The production of various meat substitutes (plantbased, mycoprotein-based, dairy-based, and animal-based substitutes) aims to reduce the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
289
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(308 citation statements)
references
References 25 publications
13
289
0
6
Order By: Relevance
“…The high environmental impacts connected with meat production and the increase in demand up till 2050 require dietary changes. Insect-based meat substitutes are potentially more sustainable but require more advanced cultivation and processing techniques (Smetana et al 2015). Such advancement is expected as the whole sector of insects as food and feed is just emerging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high environmental impacts connected with meat production and the increase in demand up till 2050 require dietary changes. Insect-based meat substitutes are potentially more sustainable but require more advanced cultivation and processing techniques (Smetana et al 2015). Such advancement is expected as the whole sector of insects as food and feed is just emerging.…”
Section: Discussionmentioning
confidence: 99%
“…On most reported aspects cricket production had a similar or lower impact than poultry production. Smetana et al (2015) compared the environmental impact of several meat substitutes, based on a similarly large selection of indicators. They concluded that insect-based and soy meal-based products were associated with the lowest environmental impact.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study on meat substitutes has shown that labgrown meat performs considerably worse than chicken meat and dairy milk, whereas edible insects are beneficial for the environment. Soya meal-based substitutes represent the most environmentally friendly alternative (Smetana et al 2015). Table 6 Numerous studies have shown that a diet with less animal products and especially a vegan diet benefits the environment (e.g.…”
Section: Trade-offs With Environmental Impactsmentioning
confidence: 99%
“…While the sustainability and nutritional benefits of meat substitute products are often highlighted at an individual dietary level (Denny et al, 2008;Smetana et al, 2015), no comprehensive analysis has been conducted on the overall scale of these benefits at the national, regional and international level.…”
Section: Introductionmentioning
confidence: 99%